Application of Digital-Based Video Media in Improving Learning Outcomes in Madrasah in Central Kalimantan - Rodhatul Jennah; Muhammad Redha Anshari; Siti Khodijah (Ta'dib, 2024)
This study investigates the effectiveness of video-based digital media in enhancing student learning outcomes in Central Kalimantan madrasahs. Using a quantitative approach with a sample of 20 students from MAN Palangka Raya and MAN East Kotawaringin, data were collected through observation, questionnaires, interviews, and documentation. Statistical analysis shows a significant improvement in learning outcomes, with an increase of 14.9% from pre-test to post-test scores, achieving an average learning outcome of 82.8%. These findings indicate that video-based media can positively impact student engagement and understanding, suggesting its potential for broader application in digital learning environments within Indonesian madrasahs